2003
DOI: 10.1016/s0002-9440(10)63454-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Calcium-Binding Proteins MRP8 and MRP14 in Inflammatory Muscle Diseases

Abstract: The pathophysiological role of infiltrating macrophages and their subtypes in idiopathic inflammatory myopathies such as dermatomyositis, polymyositis, and inclusion body myositis is not fully clear. Monocytes exhibit various phenotypes with different functional properties such as release of pro-or anti-inflammatory mediators. Expression of myeloid-related proteins MRP8 and MRP14, two calcium-binding S100-proteins, characterizes a proinflammatory subtype of macrophages. We immunohistochemically investigated ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 55 publications
2
60
0
1
Order By: Relevance
“…12,[23][24][25][26][27][28][29][30][31][32] Patients with diabetes mellitus have high plasma levels of MRP8/14. 33 Most recently, it has been reported that increasing plasma concentrations of MRP8/14 among healthy individuals can predict the risk of future cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…12,[23][24][25][26][27][28][29][30][31][32] Patients with diabetes mellitus have high plasma levels of MRP8/14. 33 Most recently, it has been reported that increasing plasma concentrations of MRP8/14 among healthy individuals can predict the risk of future cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activated macrophages promote destruction and impair regeneration via secretion of S100A8 and S100A9 in inflammatory muscle diseases (135), and blockade of RAGE restores effective cutaneous wound healing in diabetic mice (136). …”
Section: Alarmins As Regenerative Therapymentioning
confidence: 99%
“…S100A8 belongs to the S100 protein family and originates from neutrophil granulocytes and macrophages. This protein favors cell growth and restrains proliferation, has the ability to mediate apoptosis and enzymatic activity, promotes a dynamic cytoskeleton, maintains calcium ion stability, and stimulates the development of cancer (15,16). In recent years, S100A8 has been found to be able to regulate inflammatory activity and S100A8 is overexpressed in many infectious diseases (17).…”
Section: Identification Of Differentially Expressed Proteinsmentioning
confidence: 99%